Microbial transmission in animal social networks and the social microbiome - Sarkar, A; Harty, S; Johnson, KV-A; Moeller, AH; Archie, EA; Schell, LD; Carmody, RN; Clutton-Brock, TH; Dunbar, RIM; Burnet, PWJ (Springer Nature, 2020)
Host-associated microbiomes play an increasingly appreciated role in animal metabolism, immunity and health. The microbes in turn depend on their host for resources and can be transmitted across the host's social network. In this Perspective, we describe how animal social interactions and networks may provide channels for microbial transmission. We propose the 'social microbiome' as the microbial metacommunity of an animal social group. We then consider the various social and environmental forces that are likely to influence the social microbiome at multiple scales, including at the individual level, within social groups, between groups, within populations and species, and finally between species. Through our comprehensive discussion of the ways in which sociobiological and ecological factors may affect microbial transmission, we outline new research directions for the field.